The European Sleep Apnoea Database (ESADA) ERS Clinical Research Collaboration: past, present and future. Issue 4 (11th October 2018) - Bonsignore, Maria R.; Hedner, Jan
The European Sleep Apnoea Database (ESADA) study began in 2007 as a joint project within the European Union (EU) Cooperation in Science and Technology (COST) Action B26 on obstructive sleep apnoea (OSA) and cardiovascular risk, as a network of nationally appointed sleep apnoea experts. At that time, there were few cohorts of OSA patients, mainly in the context of epidemiological studies in the general population [1–6]. The COST Action only provided funding for networking, and each participating centre entered data into the web-based database on a voluntary basis. Collected data included anthropometrics, results of blood tests, current medications, and sleep data derived from full polysomnography or cardiorespiratory nocturnal monitoring, according to the diagnostic procedure chosen by the physician. Importantly, quality controls of the dataset were performed at regular intervals since the start of the project. The European Sleep Apnoea Database (ESADA) ERS Clinical Research Collaboration records data in over 25 000 patients with OSA from 33 European countries, to conduct clinical research and improve OSA patient care and outcomes http://ow.ly/DuDf30lZRP6